High-strength gelatin-based artificial board adhesive and preparation method thereof

Through dual cross -linking technology and combined with chemical and physical cross -linking agents, high -strength messenging artificial plate adhesives are prepared, which solves the problem of insufficient water resistance and adhesion strength of existing gelatin adhesives, and realizes excellent Water resistance and regulatory processability.

CN119371933AInactive Publication Date: 2025-01-28菏泽市林业产业发展中心
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411751141.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119371933A_ABST
    Figure CN119371933A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength gelatin-based artificial board adhesive and a preparation method thereof, and aims at solving the problems that an existing gelatin-based adhesive is poor in water resistance and not high in bonding strength, and processability is not easy to regulate and control. Gelatin is used as a main raw material, dialdehyde starch and waterborne polyamide epichlorohydrin are combined as cross-linking agents, magnesium-aluminum hydrotalcite is used as a modified filler, fenugreek gum is used as a tackifier, polyvinyl alcohol is used as a modification additive, and the high-strength gelatin-based adhesive is prepared through a specific process. The preparation method comprises the following specific steps: preparing a gelatin aqueous solution, a fenugreek gum tackifier, a polyvinyl alcohol aqueous solution and dialdehyde starch, and uniformly mixing the components to obtain the adhesive. According to the technical scheme, through multiple crosslinking effects, the adhesive is endowed with excellent bonding strength, water resistance and good processability, the raw materials are environment-friendly and non-toxic, the adhesive is suitable for manufacturing artificial boards such as plywood, and the quality and performance of the artificial boards are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood adhesives, and particularly relates to a high-strength gelatin-based artificial board adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of society and the growing demand for artificial boards, the annual output of artificial boards (such as plywood, particleboard, fiberboard) in my country has exceeded 310 million cubic meters. The adhesives used to make these artificial boards are mainly "trialdehyde glue" (urea-formaldehyde resin, phenol-formaldehyde resin and melamine formaldehyde resin). However, "trialdehyde glue" is synthesized from non-renewable petrochemical resources and will continuously release formaldehyde that threatens human health during use.

[0003] As people's awareness of environmental safety increases, the development of renewable, low-aldehyde or even formaldehyde-free environmentally friendly adhesives has attracted people's attention. Gelatin is a resource-rich, renewable natural polymer material that can be derived from animal skin, bones and other tissues. Its molecular structure contains hydrophilic active groups such as amino (-NH2), hydroxyl (-OH), and carboxyl (-COOH). The presence of these polar groups, on the one hand, enables it to form physical adsorption such as hydrogen bonds with the wood matrix, giving gelatin-based adhesives good dry bonding strength, and on the other hand, it makes gelatin-based adhesives have the defect of poor water resistance.

[0004] Chemical crosslinking is a common method to improve the water resistance and bonding strength of gelatin-based adhesives. However, the commonly used chemical crosslinking agents, such as water-based epoxy latex, polyamide epichlorohydrin, and glyoxal, have the disadvantage of limited crosslinking efficiency when crosslinking modified gelatin alone. The application period of isocyanate-crosslinked modified gelatin is too short and the adhesive layer is brittle. Traditional modified gelatin adhesives with only physical crosslinking (hydrogen bonding, van der Waals force) are easily damaged in humid or water environments, showing unsatisfactory water resistance. Therefore, a method for preparing an environmentally friendly high-strength gelatin-based adhesive by multiple crosslinking is proposed. Summary of the invention

[0006] The present invention is to solve the problems of existing gelatin-based adhesives having unsatisfactory water resistance, low bonding strength, and difficult viscosity regulation, and proposes a method for preparing an environmentally friendly high-strength gelatin-based artificial board adhesive by a double cross-linking method. Among them, dialdehyde starch has a chemical cross-linking effect on gelatin, magnesium aluminum hydrotalcite can form a metal coordination bond with gelatin, PVA can form a physical hydrogen bond with gelatin and dialdehyde starch, water-based polyamide epichlorohydrin can form a chemical cross-linking network with gelatin and dialdehyde starch, and fenugreek gum has the function of regulating the viscosity and processability of the system. The present invention forms physical and chemical cross-linking with gelatin to give the gelatin-based adhesive excellent bonding strength, water resistance and adjustable processability.

[0007] The technical solution adopted by the present invention is: A method for preparing a high-strength gelatin-based wood-based panel adhesive, characterized in that it specifically comprises the following steps, wherein the following amounts are all in parts by mass: Step 1: Preparation of gelatin aqueous solution Add 2 parts of modifier to 100 parts of water, heat to 65°C while stirring, then add 100-150 parts of gelatin, keep the temperature at 65°C for 1-2 hours, and obtain a gelatin aqueous solution with a solid content of 50%-60%; Step 2: Preparation of Fenugreek Gum Thickener Slowly add 5 parts of alkaline substance to 100 parts of water while stirring. After it is completely dissolved, slowly add 3-5 parts of fenugreek gum within 15 minutes. After adding, keep the temperature at 80-90° C. for 3-5 hours. After cooling, a fenugreek gum thickener with a solid content of about 2-5% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution 15 parts of polyvinyl alcohol and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 85°C-95°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15% was obtained; Step 4: Preparation of dialdehyde starch Disperse 10 parts of starch in 50-100 parts of water, then add NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit is 1.2:1), adjust the solution pH to 3.5 with sulfuric acid, stir mechanically at 40°C and 550 rpm, and react in the dark for 60-72 hours. After cooling, filter and obtain the crude dialdehyde starch product. Add water to wash and filter again until the iodate ions are completely removed, continue to dissolve the sample in anhydrous ethanol, filter and dry in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0008] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive 100 parts of the gelatin aqueous solution obtained in step 1, 0.5-2 parts of the fenugreek gum thickener obtained in step 2, 10-20 parts of the polyvinyl alcohol solution obtained in step 3, 5-10 parts of the dialdehyde starch obtained in step 4, 0.5-1.5 parts of hydrotalcite, 5-10 parts of an aqueous crosslinking agent, and 1-2 parts of an antibacterial agent are uniformly stirred to obtain a double-crosslinked gelatin-based adhesive.

[0009] In the step 5, the gelatin aqueous solution, the polyvinyl alcohol solution and the dialdehyde starch are first stirred at a speed of 200 rpm for 10-20 minutes, then the hydrotalcite and the antibacterial agent are added while stirring, and finally the cross-linking agent and the fenugreek gum thickener are added and stirred for 15-30 minutes.

[0010] In the step 1, the modifier is one or more combinations of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0011] In the step 2, the alkaline substance is a complex of sodium hydroxide or potassium hydroxide and calcium oxide.

[0012] In the step 2, the mass ratio of the alkaline substance sodium hydroxide or potassium hydroxide to calcium oxide is 1:1.

[0013] In the step 5, the polyvinyl alcohol is PVA-1799 with a degree of polymerization of 1700 and a degree of alcoholysis of 99%.

[0014] In the step 5, the hydrotalcite is magnesium-aluminum hydrotalcite.

[0015] In the step 5, the antibacterial agent is one or more of Litsea cubeba essential oil, Moringa oleifera essential oil, Sage essential oil, Tsaoko essential oil, Cuminum cumin essential oil, Zanthoxylum bungeanum essential oil and Bamboo leaf essential oil.

[0016] In the step 5, the water-based crosslinking agent is polyamide epichlorohydrin (PAE) with a solid content of 20 wt%.

[0017] Compared with the prior art solutions, the present invention has at least the following beneficial effects: (1) The raw materials selected in the present invention, such as gelatin, dialdehyde starch, and fenugreek gum, are all biomass resources, which are abundant, environmentally friendly, and non-toxic, and can help alleviate the shortage of petrochemical resources.

[0018] (2) The present invention uses both the crosslinking agent dialdehyde starch and the water-based polyamide epichlorohydrin to chemically crosslink and modify gelatin, thereby giving the gelatin-based adhesive excellent water resistance and bonding strength.

[0019] (3) The present invention introduces polyvinyl alcohol and magnesium aluminum hydrotalcite to modify gelatin, forming hydrogen bonding and metal coordination in the adhesive system, which, combined with chemical cross-linking, endows the gelatin-based adhesive with outstanding bonding strength and water resistance.

[0020] (4) The fenugreek gum used in the present invention has good compatibility with the gelatin solution, can regulate the viscosity and processability of the adhesive system, and is conducive to the sizing and preparation of different types of artificial boards. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the sample for testing the bonding strength of three-layer plywood. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific embodiments. The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0024] Example 1 Step 1: Preparation of gelatin aqueous solution According to the mass fraction, 2 parts of sodium dodecyl sulfate were added to 100 parts of water, and the mixture was heated to 65°C while being stirred. Then, 100 parts of gelatin were added, and the mixture was kept at 65°C for 1 hour to obtain a gelatin aqueous solution with a solid content of 49.8%. Step 2: Preparation of Fenugreek Gum Thickener Slowly add 0.5 parts of sodium hydroxide and 0.5 parts of calcium oxide to 100 parts of water while stirring. After they are completely dissolved, slowly add 3 parts of fenugreek gum within 15 minutes. After the addition, keep the temperature at 80° C. for 3 hours. After cooling, a fenugreek gum thickener with a solid content of about 3.8% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution According to the mass fraction, 15 parts of polyvinyl alcohol PVA-1799 and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 85°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15.2% was obtained; Step 4: Preparation of dialdehyde starch According to the mass fraction, 10 parts of starch were dispersed in 50 parts of water, and then NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit was 1.2:1) was added, and the pH of the solution was adjusted to 3.5 with sulfuric acid. The mixture was mechanically stirred at 40°C and 550 rpm, and the reaction was protected from light for 60 hours. After cooling, the crude dialdehyde starch product was obtained by suction filtration. Water was added again for washing and suction filtration until the iodate ions were completely removed, and the sample was further dissolved in anhydrous ethanol, suction filtered, and dried in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0025] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive According to the mass proportions, 100 parts of the gelatin aqueous solution obtained in step 1, 10 parts of the polyvinyl alcohol solution obtained in step 3, and 5 parts of the dialdehyde starch obtained in step 4 were stirred at a speed of 200 rpm for 10 minutes, and then 0.5 parts of magnesium aluminum hydrotalcite and 1 part of the antibacterial agent prickly ash essential oil were added while stirring, and finally 5 parts of the water-based crosslinking agent (solid content of 20 wt%) polyamide epichlorohydrin and 0.5 parts of the fenugreek gum thickener obtained in step 2 were added and stirred for 15 minutes to obtain a double-crosslinked gelatin-based adhesive.

[0026] Example 2 Step 1: Preparation of gelatin aqueous solution According to the mass fraction, 2 parts of sodium dodecyl sulfate were added to 100 parts of water, and heated to 65°C while stirring, and then 110 parts of gelatin were added, and the reaction was maintained at 65°C for 1.2 hours to obtain a gelatin aqueous solution with a solid content of 52.9%; Step 2: Preparation of Fenugreek Gum Thickener Slowly add 0.5 parts of sodium hydroxide and 0.5 parts of calcium oxide to 100 parts of water while stirring. After they are completely dissolved, slowly add 4 parts of fenugreek gum within 15 minutes. After the addition, keep the temperature at 80° C. for 4 hours. After cooling, a fenugreek gum thickener with a solid content of about 4.7% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution According to the mass fraction, 15 parts of polyvinyl alcohol PVA-1799 and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 90°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15.5% was obtained; Step 4: Preparation of dialdehyde starch According to the mass fraction, 10 parts of starch were dispersed in 60 parts of water, and then NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit was 1.2:1) was added, and the pH of the solution was adjusted to 3.5 with sulfuric acid. The mixture was mechanically stirred at 40°C and 550 rpm, and the reaction was protected from light for 62 hours. After cooling, the crude dialdehyde starch product was obtained by suction filtration. Water was added again for washing and suction filtration until the iodate ions were completely removed, and the sample was further dissolved in anhydrous ethanol, suction filtered, and dried in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0027] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive According to the mass proportions, 100 parts of the gelatin aqueous solution obtained in step 1, 12 parts of the polyvinyl alcohol solution obtained in step 3, and 6 parts of the dialdehyde starch obtained in step 4 were stirred at a speed of 200 rpm for 10 minutes, and then 0.7 parts of magnesium aluminum hydrotalcite and 1.2 parts of the antibacterial agent prickly ash essential oil were added while stirring, and finally 6 parts of the water-based crosslinking agent (solid content of 20 wt%) polyamide epichlorohydrin and 0.7 parts of the fenugreek gum thickener obtained in step 2 were added and stirred for 15 minutes to obtain a double-crosslinked gelatin-based adhesive.

[0028] Example 3 Step 1: Preparation of gelatin aqueous solution According to the mass fraction, 2 parts of sodium dodecyl sulfate were added to 100 parts of water, and heated to 65°C while stirring, and then 120 parts of gelatin were added, and the reaction was maintained at 65°C for 1.4 hours to obtain a gelatin aqueous solution with a solid content of 54.1%; Step 2: Preparation of Fenugreek Gum Thickener Slowly add 0.5 parts of sodium hydroxide and 0.5 parts of calcium oxide to 100 parts of water while stirring. After they are completely dissolved, slowly add 4 parts of fenugreek gum within 15 minutes. After the addition, keep the temperature at 85°C for 4 hours. After cooling, a fenugreek gum thickener with a solid content of about 4.8% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution According to the mass fraction, 15 parts of polyvinyl alcohol PVA-1799 and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 90°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 14.8% was obtained; Step 4: Preparation of dialdehyde starch According to the mass fraction, 10 parts of starch were dispersed in 70 parts of water, and then NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit was 1.2:1) was added, and the pH of the solution was adjusted to 3.5 with sulfuric acid. The mixture was mechanically stirred at 40°C and 550 rpm, and the reaction was protected from light for 64 hours. After cooling, the crude dialdehyde starch product was obtained by suction filtration. Water was added again for washing and suction filtration until the iodate ions were completely removed, and the sample was further dissolved in anhydrous ethanol, suction filtered, and dried in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0029] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive According to the mass proportions, 100 parts of the gelatin aqueous solution obtained in step 1, 14 parts of the polyvinyl alcohol solution obtained in step 3, and 7 parts of the dialdehyde starch obtained in step 4 were stirred at a speed of 200 rpm for 10 minutes, and then 0.9 parts of magnesium aluminum hydrotalcite and 1.4 parts of the antibacterial agent prickly ash essential oil were added while stirring, and finally 7 parts of the water-based crosslinking agent (solid content of 20 wt%) polyamide epichlorohydrin and 0.9 parts of the fenugreek gum thickener obtained in step 2 were added and stirred for 15 minutes to obtain a double-crosslinked gelatin-based adhesive.

[0030] Example 4 Step 1: Preparation of gelatin aqueous solution According to the mass fraction, 2 parts of sodium dodecyl sulfate were added to 100 parts of water, and heated to 65°C while stirring, and then 135 parts of gelatin were added, and the reaction was maintained at 65°C for 1.8 hours to obtain a gelatin aqueous solution with a solid content of 57.9%; Step 2: Preparation of Fenugreek Gum Thickener Slowly add 0.5 parts of sodium hydroxide and 0.5 parts of calcium oxide to 100 parts of water while stirring. After they are completely dissolved, slowly add 4 parts of fenugreek gum within 15 minutes. After the addition, keep the temperature at 90° C. for 4 hours. After cooling, a fenugreek gum thickener with a solid content of about 4.8% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution According to the mass fraction, 15 parts of polyvinyl alcohol PVA-1799 and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 95°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15.3% was obtained; Step 4: Preparation of dialdehyde starch According to the mass fraction, 10 parts of starch were dispersed in 85 parts of water, and then NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit was 1.2:1) was added, and the pH of the solution was adjusted to 3.5 with sulfuric acid. The mixture was mechanically stirred at 40°C and 550 rpm, and the reaction was protected from light for 68 hours. After cooling, the crude dialdehyde starch product was obtained by suction filtration. Water was added again for washing and suction filtration until the iodate ions were completely removed, and the sample was further dissolved in anhydrous ethanol, suction filtered, and dried in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0031] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive According to the mass proportions, 100 parts of the gelatin aqueous solution obtained in step 1, 18 parts of the polyvinyl alcohol solution obtained in step 3, and 8.5 parts of the dialdehyde starch obtained in step 4 were stirred at a speed of 200 rpm for 20 minutes, and then 1.2 parts of magnesium aluminum hydrotalcite and 1.75 parts of the antibacterial agent prickly ash essential oil were added while stirring, and finally 8.5 parts of the water-based crosslinking agent (solid content of 20 wt%) polyamide epichlorohydrin and 1.5 parts of the fenugreek gum thickener obtained in step 2 were added and stirred for 30 minutes to obtain a double-crosslinked gelatin-based adhesive.

[0032] Example 5 Step 1: Preparation of gelatin aqueous solution According to the mass fraction, 2 parts of sodium dodecyl sulfate were added to 100 parts of water, and the mixture was heated to 65°C while being stirred. Then, 150 parts of gelatin were added, and the mixture was kept at 65°C for 2 hours to obtain a gelatin aqueous solution with a solid content of 60.5%. Step 2: Preparation of Fenugreek Gum Thickener Slowly add 0.5 parts of sodium hydroxide and 0.5 parts of calcium oxide to 100 parts of water while stirring. After they are completely dissolved, slowly add 5 parts of fenugreek gum within 15 minutes. After the addition, keep the temperature at 90° C. for 5 hours. After cooling, a fenugreek gum thickener with a solid content of about 5.7% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution According to the mass fraction, 15 parts of polyvinyl alcohol PVA-1799 and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 95°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15.7% was obtained; Step 4: Preparation of dialdehyde starch According to the mass fraction, 10 parts of starch were dispersed in 100 parts of water, and then NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit was 1.2:1) was added, and the pH of the solution was adjusted to 3.5 with sulfuric acid. The mixture was mechanically stirred at 40°C and 550 rpm, and the reaction was carried out in the dark for 72 hours. After cooling, the crude dialdehyde starch product was obtained by suction filtration. Water was added again for washing and suction filtration until the iodate ions were completely removed, and the sample was further dissolved in anhydrous ethanol, suction filtered, and dried in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch.

[0033] Step 5: Preparation of high-strength gelatin-based wood-based panel adhesive According to the mass proportions, 100 parts of the gelatin aqueous solution obtained in step 1, 20 parts of the polyvinyl alcohol solution obtained in step 3, and 10 parts of the dialdehyde starch obtained in step 4 were stirred at a speed of 200 rpm for 10 minutes, and then 1.5 parts of magnesium aluminum hydrotalcite and 2 parts of the antibacterial agent prickly ash essential oil were added while stirring, and finally 10 parts of the water-based crosslinking agent (solid content of 20 wt%) polyamide epichlorohydrin and 2 parts of the fenugreek gum thickener obtained in step 2 were added and stirred for 15 minutes to obtain a double-crosslinked gelatin-based adhesive.

[0034] Comparative Example 1 The only difference between this comparative example and Example 3 is that the polyamide epichlorohydrin in step 5 is removed, and the remaining raw materials and processes are the same as those in Example 3.

[0035] Comparative Example 2 The difference between this comparative example and Example 3 is that the dialdehyde starch in step 4 and step 5 is removed, and the other raw materials and processes are the same as those in Example 3.

[0036] Comparative Example 3 The only difference between this comparative example and Example 3 is that the polyvinyl alcohol PVA-1799 in step 3 and step 5 is removed, and the remaining raw materials and processes are the same as those in Example 3.

[0037] Comparative Example 4 The only difference between this comparative example and Example 3 is that the fenugreek gum thickener in step 2 and step 5 is removed, and the other raw materials and processes are the same as those in Example 3.

[0038] Comparative Example 5 The only difference between this comparative example and Example 3 is that the magnesium aluminum hydrotalcite in step 5 is removed, and the rest of the raw materials and processes are the same as those in Example 3.

[0039] Comparative Example 6 The only difference between this comparative example and Example 3 is that the modifier sodium dodecyl sulfate in step 1 is removed and gelatin is directly dissolved in hot water. The rest of the raw materials and processes are the same as those in Example 3.

[0040] Comparative Example 7 The difference between this comparative example and Example 3 is that the dialdehyde starch in step 4 and the polyamide epichlorohydrin in step 5 are removed, and the remaining raw materials and processes are the same as those in Example 3.

[0041] Comparative Example 8 The only difference between this comparative example and Example 3 is that the polyamide epichlorohydrin in step 5 is replaced by polyphenyl polymethylene polyisocyanate (p-MDI), and the other raw materials and processes are the same as those in Example 3.

[0042] Performance Testing: Adhesive solid content test: Determine by weighing method according to the national standard “Test Methods for Wood Adhesives and Their Resins” (GB / T14074.5-2006).

[0043] Adhesive viscosity test: Use a viscometer to test.

[0044] Applicable period: The applicable period is the time from the completion of adhesive preparation to the loss of fluidity and difficulty in coating.

[0045] Preparation of three-layer plywood: The adhesive prepared in the above examples and comparative examples was manually applied to the core layer of the birch veneer (the double-sided glue application amount was 300 g / m 2 ), and then the upper and lower surfaces are perpendicular to the core layer, and the three birch boards are assembled in the same direction with the loose and tight surfaces. After assembly, the three birch boards are pre-pressed at 0.8 MPa for 45 minutes, and then hot-pressed at 120-125 ℃ and 1.4 MPa for 4.5 minutes to obtain three-layer birch plywood. Then the board is cut into 32 specimens, divided into 4 parts, and its dry strength and wet strength are tested respectively.

[0046] Dry bonding strength: The plywood is Figure 1 Cut and directly carry out tensile test on the cut specimens.

[0047] 20 °C cold water immersion wet strength: According to GB / T 9846-2015 "Ordinary Plywood" standard, the cut specimens are immersed in 20 °C cold water for 24 hours, then taken out and immersed in room temperature water for 5-10 min. After the temperature of the specimens drops to room temperature, the tensile strength test is carried out.

[0048] 63 °C water soaking strength: According to GB / T 9846-2015 "Ordinary Plywood" standard, the cut specimens are soaked in a 63 °C warm water bath for 3 hours, then taken out and soaked in room temperature water for 5-10 min. After the temperature of the specimens drops to room temperature, the tensile strength test is carried out.

[0049] Boiling wet strength: According to GB / T 9846-2015 "Ordinary Plywood" standard, the cut specimens are first placed in boiling water for 3 hours, then taken out and soaked in water at room temperature for 5-10 minutes. After the temperature of the specimens drops to room temperature, the tensile strength test is carried out. Table 1 Basic properties of adhesives in comparative examples and examples Sample Viscosity (cp) Solid content (%) Applicable period Glue coating Example 1 3520±65 48.9%±0.3% >16 h good Example 2 4105±82 50.6%±0.5% >16 h good Example 3 4230±95 51.1%±0.2% >12 h good Example 4 4685±105 52.8%±0.4% >8 h good Example 5 5235±215 54.5%±0.2% >8 h good Comparative Example 1 3540±85 50.3%±0.2% >24 h good Comparative Example 2 1560±50 46.8%±0.6% >24 h good Comparative Example 3 3725±65 48.5%±0.1% <6 h good Comparative Example 4 3220±120 50.9%±0.3% >24 h good Comparative Example 5 2850±70 50.6%±0.4% >24 h good Comparative Example 6 3640±85 51.7%±0.2% >24 h good Comparative Example 7 1285±45 45.9%±0.2% >24 h good Comparative Example 8 9560±355 50.5%±0.8% <2 h Poor, difficult to apply evenly Table 2 Properties of three-layer plywood prepared with adhesives from comparative examples and examples Sample Dry strength (MPa) 24h immersion wet strength (20 ℃ cold water, MPa) 3h immersion wet strength (63℃ hot water, MPa) 3h boiling water wet strength (100℃ hot water, MPa) Example 1 1.70±0.08 1.42±0.07 1.23±0.04 1.07±0.03 Example 2 1.78±0.04 1.45±0.10 1.28±0.06 1.12±0.03 Example 3 1.96±0.12 1.65±0.09 1.32±0.05 1.23±0.04 Example 4 1.85±0.08 1.52±0.04 1.24±0.03 1.17±0.03 Example 5 1.78±0.04 1.38±0.03 1.25±0.09 1.09±0.04 Comparative Example 1 1.52±0.08 0.81±0.07 0.56±0.04 7 pieces of glue, 0 Comparative Example 2 1.59±0.12 1.03±0.06 0.85±0.05 0.35±0.05 Comparative Example 3 1.34±0.09 1.13±0.09 0.84±0.09 Completely debonded, 0 Comparative Example 4 1.72±0.04 1.08±0.24 0.96±0.29 0.65±0.09 Comparative Example 5 1.55±0.12 1.21±0.07 1.05±0.08 0.50±0.08 Comparative Example 6 1.63±0.21 1.15±0.04 0.72±0.04 6 pieces of glue, 0 Comparative Example 7 1.35±0.12 7 samples were debonded, 0 Glue opening, 0 Completely debonded, 0 Comparative Example 8 2.21±0.56 1.95±0.65 4 out of 8 specimens failed 7 out of 8 specimens failed As can be seen from Table 1, the dry bonding strength of the three-layer birch plywood prepared by the modified gelatin-based adhesive of the present invention is greater than 1.70 MPa, and the 3h boiling water wet strength is greater than 1.07 MPa. Compared with the control group, the water resistance of the plywood prepared in the embodiment is significantly improved. According to the water resistance requirements of plywood in GB / T9846-2015 "Ordinary Plywood", the performance data of the modified gelatin-based wood adhesive of the present invention are higher than the national standard requirement (1.0 MPa). This is mainly because the modified gelatin adhesive prepared by the present invention utilizes sodium dodecyl sulfate to modify the gelatin aqueous solution, so that the reactive groups (amino, hydroxyl and carboxyl groups) in the gelatin are fully exposed, and thus, the water-based polyamide epichlorohydrin can form a chemical cross-linking network with gelatin and dialdehyde starch, the aldehyde groups in the dialdehyde starch can chemically cross-link with the amino groups of the gelatin, PVA can form a physical hydrogen bond with the gelatin and the dialdehyde starch, magnesium aluminum hydrotalcite can form a metal coordination bond with the gelatin, and fenugreek gum has the function of regulating the viscosity and curing characteristics of the system. The comprehensive effect of these substances enables the gelatin-based adhesive system to form relatively sufficient physical and chemical cross-linking, thereby giving the gelatin-based adhesive excellent bonding strength, water resistance and adjustable processability.

[0050] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength gelatin-based wood-based panel adhesive, characterized in that: Specifically include the following steps, the following amounts are all weight parts: Step 1: Preparation of gelatin aqueous solution Add 2 parts of modifier to 100 parts of water, heat to 65°C while stirring, then add 100-150 parts of gelatin, keep the temperature at 65°C for 1-2 hours, and obtain a gelatin aqueous solution with a solid content of 50%-60%; Step 2: Preparation of Fenugreek Gum Thickener Slowly add 5 parts of alkaline substance to 100 parts of water while stirring. After it is completely dissolved, slowly add 3-5 parts of fenugreek gum within 15 minutes. After adding, keep the temperature at 80-90° C. for 3-5 hours. After cooling, a fenugreek gum thickener with a solid content of about 2-5% is obtained. Step 3: Preparation of polyvinyl alcohol aqueous solution 15 parts of polyvinyl alcohol and 85 parts of water were stirred and mixed at a speed of 200 r / min, and the temperature was raised to 65°C for 30 minutes, then heated at 85°C-95°C for 2 hours, and finally cooled to 65°C for 30 minutes. After cooling, a polyvinyl alcohol solution with a solid content of about 15% was obtained; Step 4: Preparation of dialdehyde starch Disperse 10 parts of starch in 50-100 parts of water, then add NaIO4 (the molar ratio of NaIO4 to pyranose glucose unit is 1.2:1), adjust the solution pH to 3.5 with sulfuric acid, stir mechanically at 40°C and 550 rpm, react in the dark for 60-72 hours, filter after cooling to obtain the crude dialdehyde starch product, add water to wash and filter again until the iodate ions are completely removed, continue to dissolve the sample in anhydrous ethanol, filter and dry in a vacuum oven at 40°C for 24 hours to obtain dialdehyde starch; Step 5: Preparation of high-strength gelatin-based adhesive 100 parts of the gelatin aqueous solution obtained in step 1, 0.5-2 parts of the fenugreek gum thickener obtained in step 2, 10-20 parts of the polyvinyl alcohol solution obtained in step 3, 5-10 parts of the dialdehyde starch obtained in step 4, 0.5-1.5 parts of hydrotalcite, 5-10 parts of an aqueous crosslinking agent, and 1-2 parts of an antibacterial agent are uniformly stirred to obtain a double-crosslinked gelatin-based adhesive.

2. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: In step 5, the gelatin aqueous solution, the polyvinyl alcohol solution and the dialdehyde starch are first stirred at a speed of 200 rpm for 10-20 minutes, and then the hydrotalcite and the antibacterial agent are added while stirring, and finally the cross-linking agent and the fenugreek gum thickener are added and stirred for 15-30 minutes.

3. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: In step 1, the modifier is one or more combinations of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

4. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: In step 2, the alkaline substance is a complex of sodium hydroxide or potassium hydroxide and calcium oxide.

5. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: In step 2, the mass ratio of the alkaline substance sodium hydroxide or potassium hydroxide to calcium oxide is 1:

1.

6. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: The polyvinyl alcohol is PVA-1799 with a degree of polymerization of 1700 and a degree of alcoholysis of 99%.

7. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: The hydrotalcite is magnesium-aluminum hydrotalcite.

8. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: The antibacterial agent in step 5 is one or more of Litsea cubeba essential oil, Moringa oleifera essential oil, Sage essential oil, Tsaoko essential oil, Cuminum cumin essential oil, Zanthoxylum bungeanum essential oil and Bamboo leaf essential oil.

9. The method for preparing a high-strength gelatin-based wood-based panel adhesive according to claim 1, characterized in that: The aqueous crosslinking agent is polyamide epichlorohydrin with a solid content of 20 wt%.

10. An environmentally friendly water-based wood adhesive prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Dialdehyde lignin and dialdehyde protection lignin adhesive as well as preparation method and application thereof

    CN120271846A